2012
DOI: 10.5021/ad.2012.24.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Melanogenesis by Rapamycin in Human MNT-1 Melanoma Cells

Abstract: BackgroundMelanogenesis is one of the characteristic parameters of differentiation in melanocytes and melanoma cells. Specific inhibitors of phosphatidylinositol 3-kinase (PI3K), such as wortmannin and LY294002, stimulate melanin production in mouse and in human melanoma cells, suggesting that PI3K and mammalian target of rapamycin (mTOR) might be involved in the regulation of melanogenesis.ObjectiveThe involvement of the mTOR pathway in regulating melanogenesis was examined using human MNT-1 melanoma cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…Our results and those of previous studies suggest that the role of mTOR in autophagy‐mediated melanocyte regulation depends on the melanocyte cell type (Hah et al, ; Katsuyama et al, ). Topical rapamycin, a representative mTOR inhibitor, is reported to substantially improve the appearance of hypopigmented macules in patients with tuberous sclerosis, which presents with distinct mTOR activation (Wataya‐Kaneda et al, ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our results and those of previous studies suggest that the role of mTOR in autophagy‐mediated melanocyte regulation depends on the melanocyte cell type (Hah et al, ; Katsuyama et al, ). Topical rapamycin, a representative mTOR inhibitor, is reported to substantially improve the appearance of hypopigmented macules in patients with tuberous sclerosis, which presents with distinct mTOR activation (Wataya‐Kaneda et al, ).…”
Section: Discussionsupporting
confidence: 84%
“…The effect of rapamycin on melanogenesis is equivocal, with variable results depending on the melanocyte cell types (Hah et al, ; Katsuyama, Taira, Yoshioka, Okano, & Masaki, ). To account for the contrasting results regarding melanogenesis, we treated both MNT‐1 cells and primary human melanocytes with rapamycin.…”
Section: Resultsmentioning
confidence: 99%
“…This study also reveals a new and novel role of mTORC1 in the regulation of MITF-1. Two previous studies found that inhibition of mTORC1 leads to melanosome formation and expression of melanogenic genes in MNT-1 melanoma cells, probably through up-regulation of the levels of MITF-4 (Ho et al, 2011; Hah et al, 2012). However, our study is the first one to show that mTORC1 promotes sequestration of this transcription factor in the cytosol.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, treatment with an autophagy activator such as rapamycin resulted in reduced melanin contents in skin-derived NHEKs [12]. Hah et al showed that rapamycin promotes melanogenesis by the up-regulation of tyrosinase protein in melanoma cells [32]. Thus, we further addressed the effect of autophagy on melanogenesis in melanocytes by using ARP101.…”
Section: Discussionmentioning
confidence: 98%